Cytokinin‐dependent regulatory module underlies the maintenance of zinc nutrition in rice. Issue 1 (2nd July 2019) - Gao, Shaopei; Xiao, Yunhua; Xu, Fan; Gao, Xiaokai; Cao, Shouyun; Zhang, Fengxia; Wang, Guodong; Sanders, Dale; Chu, Chengcai
Summary: Zinc (Zn) deficiency is a critical problem in human nutrition. Rice is the main source of calories for nearly half the world's population but has the shortcoming, from a nutritional perspective, of being low in Zn and other essential nutrients. Here we performed analyses with cytokinin‐related mutants and transgenic lines to provide unequivocal evidence that cytokinins have a key role in controlling Zn status in plants. Transporters responsible for Zn uptake and chelators for the internal transport of Zn were strictly controlled by cytokinins. Moreover, cytokinin metabolism was regulated in a highly dynamic way in response to Zn status, which allows rice to adapt to heterogeneous Zn availability. Subsequently, fine‐tuning of cytokinin metabolism by root‐specific expression of a cytokinin degradation enzyme was able to improve both Zn nutrient and yield traits. Importantly, X‐ray fluorescence imaging revealed that the increased Zn was broadly distributed from the aleurone layer to the inner endosperm. These findings show that metabolic control of cytokinin could provide the key to breeding Zn‐enriched rice.